Acute effects of caffeinated beverages on electrocardiographic and hemodynamic parameters in young adults - Mehmet Dinçer Bilgin; Şerife Gökçe Çalışkan (Cukurova Medical Journal, 2022)
Purpose: The consumption of caffeinated beverages has significantly increased among young people in recent years. The objective of the study is to investigate the acute effects of caffeinated beverages on electrocardiographic and hemodynamic parameters of young adults. Materials and Methods: Study was designed as a non-randomized, non-placebo controlled, three-arm parallel assignment. It was conducted on 56 individuals selected from a pool of students enrolled at Aydın Adnan Menderes University. Energy drink, coffee, cola and control groups were determined according to the results of the applicant acceptance questionnaire. Blood pressure and electrocardiogram were measured before and after consuming the drinks at 30 minutes and 60 minutes. Heart rate variability was detected from electrocardiogram signal and investigated by linear analysis. Results: All caffeinated drinks increased the blood pressure. Only, heart rate was increased by energy drink and cola. There was a small increment in root-mean square differences of successive R-R intervals and the number of times successive heartbeat intervals exceed 50ms (NN50) values in coffee group. High frequency (HF) values were increased some for coffee and cola groups. But, low frequency (LF) and LF/HF values were decreased. These alterations were statistically significant for coffee group. PR interval and QRS complex did not alter, however, QTc interval was lower in energy drink and cola groups. Conclusion: Caffeinated beverage consumption has the potential to induce adverse effects on cardiovascular system of young adults. Coffee appears to be more prominent than energy drink and cola.